Updated nomenclature and taxonomic status of the plants of Bangladesh included in Hook. f., the Flora of British India: Volume-II - Rashid, M. Enamur; Rahman, M. Atiqur (Bangladesh Journal of Plant Taxonomy, 2012)
Sir Joseph Dalton Hooker in his second volume of the Flora of British India included a total of 2328 species in 416 genera under 28 natural orders (= families) of which 201 species in 104 genera under 20 natural orders are determined to have been recorded from the area now in Bangladesh. These taxa are listed with their updated nomenclature and taxonomic status as per ICBN following Cronquists system of plant classification. The current nomenclatural treatment revealed a total of 200 species in 109 genera under 25 families to be recognized from the area of Bangladesh. The recorded area and the name of specimens collector, as in the protologue of the Flora of British India, are also provided. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13133 Bangladesh J. Plant Taxon. 19(2): 173-190, 2012 (December)